Generative Processes in Music: The Psychology of Performance, Improvisation, and Composition - Sloboda, John A. (New York Clarendon Press, 2001)
Where most of the literature in the psychology of music has focused on the processes involved when listening to music, little has been written about the processes involved in making music. Reissued by popular demand, and for the first time in paperback, Generative Processes: The Psychology of Performance, Improvisation, and Composition brings together leading figures in music psychology to present pioneering studies of the processes by which music is generated. The book looks at the generation of expression in musical performance, the problems of synchrony in ensemble performance, the development of children's song, rehearsal strategies of pianists, improvisational skill in trained and untrained musicians, children's spontaneous notations for music, formal constraints on compositional systems, and compositional strategies of music students. Edited by the leading authority on music psychology, the book will be of great interest to cognitive and developmental psychologists, as well as music educators and musicologists.
Keywords: Music psychology; Performance; Composing; Improvisation